2D materials for solar fuels via artificial photosynthesis. Issue 5 (2nd July 2021) - Du, Jian; Yang, Hao; Sun, Licheng
Abstract : To accelerate the chemical processes of water splitting, CO2 reduction and N2 fixation in artificial photosynthetic systems, various strategies to improve the properties of 2D materials with catalysts are highlighted in this perspective.